Rainbow of laziness - Zakaria, Zainuddin (Fakulti Pengurusan Perniagaan, UiTM Terengganu, 2021)
Do you sometimes feel that you don’t want to get out of bed and spend the whole day sleeping or relaxing in front of television? You may feel that you're lazy and hoping that somebody’ll take over and finish the very tasks or activities that you’ve planned to do. Well! We may have experienced these unproductive days and felt guilty later for being lazy. Is there any explanation to this phenomenon? First, let’s look at the psychological background of laziness.